Automation, Research Technology, and Researchers’ Trajectories: Evidence from Computer Science and Electrical Engineering - Furman, Jeffrey L.; Teodoridis, Florenta (Organization Science, 2020)
We examine how the introduction of a technology that automates research tasks influences the rate and type of researchers’ knowledge production. To do this, we leverage the unanticipated arrival of an automating motion-sensing research technology that occurred as a consequence of the introduction and subsequent hacking of the Microsoft Kinect system. To estimate whether this technology induces changes in the type of knowledge produced, we employ novel measures based on machine learning (topic modeling) techniques and traditional measures based on bibliometric indicators. Our analysis demonstrates that the shock associated with the introduction of Kinect increased the production of ideas and induced researchers to pursue ideas more diverse than and distant from their original trajectories. We find that this holds for both researchers who had published in motion-sensing research prior to the Kinect shock (within-area researchers) and those who did not (outside-area researchers), with the effects being stronger among outside-area researchers.